(untitled) (Journal of the Management Sciences, 2024)
This study investigates the relationship between job sharing and customer satisfaction and the relationship between flex time and employee retention within media firms. Using a survey design, the study examines the impact of these workplace flexibility practices on organizational performance. The study used a census sampling technique and 211 respondents were selected from media firms in Anambra State. The primary data were generated using a structured questionnaire. The analysis was performed using the Pearson correlation coefficient. The result showed a significant positive relationship between job sharing and customer satisfaction, and between flex time and employee retention. The study concludes that these flexible work arrangements can enhance employee engagement and satisfaction, thereby improving overall organizational performance. Based on these, the study recommends that media firms should actively promote job sharing as a strategy to improve customer satisfaction. This can help employees maintain a work-life balance, leading to better job performance and higher customer satisfaction. Secondly, firms should implement flex time policies to retain top talent. Hence allowing employees to choose their work hours, firms can reduce turnover rates and increase employee loyalty.